Education and the environment : policy, trends and the problems of marginalisation - Gough, Annette (Camberwell, Vic. : Australian Council for Educational Research, 1997)
The emergence of environmental education: a'history' of the field. Contemporary Australian policies on environmental education. Environmental education in a climate of educational change. Exploring alternative perspectives. Ongoing issues and challenges for the future.
Keywords: Australia; Environmental education; Environmental education -- Australia; Environmental education -- Government policy -- Australia